Productivity Standards and the Impact on Quality of Care: A National Survey of Inpatient Rehabilitation Professionals - Leslie E. Bennet; Vanessa D. Jewell; Linda Scheirton; Molly McCarthy; Brittney C. Muir (Scholarworks @ WMU, 2019)
Background: Skyrocketing health care costs have resulted in significant changes to reimbursement rates in health care. The result has increased pressure to be as efficient as possible while maintaining high-quality care. The purpose of this exploratory study was to examine health care professionals' perceptions on whether and how productivity pressures have impacted the quality of care in therapy practice. Method: A survey was disseminated nationally to inpatient rehabilitation facilities. Results: Two hundred and fifty-seven surveys were opened. Of these completed surveys, 154 participants completed the closed-ended questions and 109 participants completed the open-ended questions. Outcomes indicated that clinicians are concerned that growing productivity pressures are impacting the quality of care that they provide. In addition, the findings are consistent with the literature that an emphasis to maintain productivity standards is resulting in unprofessional practices. Conclusion: Further research needs to be conducted to generalize these findings to the larger health care network. More advocacy for policy changes and the need for a unified strategic plan among the rehabilitation professions is indicated.